Wringer - Spinelli, Jerry (New York : HarperCollins, 1997)
As Palmer comes of age, he must either accept the violence of being a wringer at his town's annual Pigeon Day or find the courage to oppose it.
Wilson's Children, October 2010.
Wilson's Junior High School, April 2001.
Elem. School Library Collection, June 2000.
School Library Journal starred, January 2000.
Notable/Best Books (A.L.A.), January 1998.
Book Links (A.L.A.), September 1999.
Keywords: Courage -- Fiction; Violence -- Fiction; Pigeons -- Fiction; Newbery honor book; Courage -- Juvenile fiction; Violence -- Juvenile fiction; Pigeons -- Juvenile fiction